Layla Majnun: Literature Psychological Study - Megan Asri Humaira (Universitas Djuanda, 2019)
Novel works usually raise various phenomena that occur in the community. These interesting works can influence the soul of the reader so that they can dive in and appear to be present in the story. In literary psychology,novel is Laila Majnun's very appropriate to study because it can see the psychological phenomenon experienced by the main character of the story, Layla and Majnun. The method used in this research is descriptive qualitative method. Representation of human behavior seen through the figures Majnun, Layla, and Syed Omri who experienced chronic frustration, so that ended in death.